Meningkatkan Pemahaman Konsep IPS Peserta Didik Kelas Iv di SDN Kenari 07 Melalui Model Pembelajaran Discovery Learning - Vina Febriana; Mahmud Yunus; Iva Sarifah (Mataram University, 2026)
This research was motivated by the low understanding of social studies (IPS) concepts among grade IV-A students at SDN Kenari 07, who tended to be passive and less actively involved in the learning process. To overcome this problem, the Discovery Learning model was implemented. This study aimed to improve the understanding of social studies concepts of grade IV-A students at SDN Kenari 07 through the implementation of the Discovery Learning model on cultural diversity materials. This type of research was Classroom Action Research (CAR) using the Kemmis & McTaggart model conducted in two cycles. The research subjects consisted of 32 grade IV-A students at SDN Kenari 07. Data were collected through tests, observations, and documentation, then analyzed qualitatively using the Miles and Huberman model and quantitatively using descriptive analysis. The results showed an increase in each cycle. Teacher activity increased from 79.90% in Cycle I to 89.71% in Cycle II. Similarly, student activity increased from 74.51% in Cycle I to 88.73% in Cycle II. This improvement had a positive impact on the classical completeness of students' conceptual understanding, which rose from 59.38% in Cycle I to 84.38% in Cycle II. In conclusion, the implementation of the Discovery Learning model successfully improved the understanding of social studies concepts of grade IV-A students at SDN Kenari 07 on cultural diversity materials.